In Vitro and In Vivo Comparison of Changes in Antibiotics Susceptibility of E. coli and Chicken’s Intestinal Flora after Exposure to Amoxicillin or Thymol - Soukayna Hriouech; Ahmed A. Akhmouch; Mariam Tanghort; Hanane Chefchaou; Aouatef Mzabi; Najat Chami; Adnane Remmal (Veterinary Medicine International)
This study aims at verifying, in vitro, the extent to which the use of amoxicillin or thymol induces the selection of resistant bacteria and at evaluating in vivo their effects on the development of antimicrobial resistance in the intestinal flora of poultry. E. coli strain was subcultured on agar plates containing increasing concentrations of either amoxicillin or thymol. Thereafter, minimal inhibitory concentrations (MICs) of thymol, amoxicillin, and two other antibiotics, tylosin and colistin, were determined using the microdilution method. Groups of chicks were subjected to a 2-week regime of either amoxicillin or thymol added to their drinking water. During the treatment with either thymol or amoxicillin, the total aerobic mesophilic flora (TAMF) was counted on thymol-gradient plates or amoxicillin-gradient plates and the MICs of antibiotics and thymol for E. coli isolates were determined. The in vitro test showed that for E. coli, which had been serially subcultured on increasing concentrations of amoxicillin, a 32-fold increase in MIC values for amoxicillin and a 4-fold increase for colistin and tylosin were noted. However, the MIC of thymol for this strain remained constant. For the E. coli, which had been serially subcultured on increasing concentrations of thymol, no change in the MIC values for antibiotics and thymol was observed. The in vivo test confirmed the in vitro one. It demonstrated that exposure to amoxicillin induced a selection of antimicrobial resistance in TAMF and intestinal E. coli, whereas exposure to thymol did not. The results showed that the group receiving thymol had a lower consumption index compared to the other groups. This study demonstrates the feasibility of this natural product as an alternative solution to the current use of antibiotics in poultry farming.